Direktif dan Ekspresif dalam Animasi "Jumbo” terhadap Dinamika Komunikasi Tokoh - Hana Pertiwi; Glory Kiswatara; Indra Perdana (Lingua Franca, 2026)
This study aims to describe the forms of directive and expressive speech acts and to explain the communication dynamics among characters in the Indonesian animated film Jumbo (2025). This research employs a descriptive qualitative method using observation and note-taking techniques. The data consist of utterances from the characters that contain directive and expressive speech acts. The analysis is based on Searle’s speech act theory (1975), Ibrahim’s classification of directives (1993), and Tarigan’s classification of expressives (2009). The findings reveal a total of 153 speech acts, consisting of 78 directive speech acts and 75 expressive speech acts. Directive speech acts include requests, commands, questions, advice, prohibitions, and granting permissions, with requests being the most dominant form. Meanwhile, expressive speech acts include praising, complaining, blaming, apologizing, expressing gratitude, offering condolences, and giving congratulations, with praising being the most frequently used form. The results show that directive speech acts function to build cooperation and influence among characters, while expressive speech acts serve to express the characters’ attitudes and feelings. Thus, the communication dynamics in Jumbo are shaped through relationships of solidarity, conflict, and reconciliation, which are manifested through the use of directive and expressive speech acts.